Effect of Selected Volatiles on Two Stored Pests: The Fungus Fusarium verticillioides and the Maize Weevil Sithophilus zeamais - Zunino, María Paula (2015)
New agronomic practices and technology enabled Argentina a larger production of cereal grains, reaching a harvest yield of 26.5 million metric tons of maize, of which, about 40% was exported. However, much of the maize production is lost annually by the attack of fungi and insects (2.6 million tons). In this study, the antifungal effect of selected volatiles on Fusarium verticillioides, its mycotoxin production, and the repellent and insecticidal activities against the weevill Sithophilus zeamais, an insect vector of F. verticillioides, were evaluated. The compounds tested were (2E)-2-hexenal, (2E)-2-nonenal,(2E,6Z)-2,6-nonadienal, 1-pentanol, 1-hexanol, 1-butanol, 3-methyl-1-butanol, pentanal, 2-decanone, and 3-decanone, which occur in the blend of volatile compounds emitted by various cereal grains. The most active antifungals were the aldehydes (2E)-2-nonenal, (2E)-2-hexenal, and (2E,6Z)-2,6-nonadienal (minimum inhibitory concentration values of <0.03, 0.06, and 0.06 mM,respectively). The occurrence of fumonisin B1 also was prevented because these compounds completely inhibited fungal growth.The best insecticidal fumigant activities against the maize weevil were shown by 2-decanone and 3-decanone (lethal concentration ≤ 54.6 μL/L (<0.28 mM)). Although, all tested compounds showed repellent activity against S. zeamais at a concentration of 4 μL/L, (2E,6Z)-2,6-nonadienal was the most active repellent compound. These results demonstrate the potential of (2E,6Z)-2,6-nonadienal to be used as a natural alternative to synthetic pesticides on F. verticillioides and S. zeamais.